2023
DOI: 10.1177/10998004231152849
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiogram Abnormalities Associated With Metabolic Syndrome: The Hispanic Community Health Study/Study of Latinos

Abstract: Background Metabolic syndrome (MetS) is a prognostic cluster of physiologic risk factors that may develop into cardiovascular disease (CVD) and type 2 diabetes mellitus (T2DM). Electrocardiogram abnormalities (ECGA) can be instrumental in identifying the early stages of disease and may be associated with MetS in Hispanic Americans. Objective To explore the relationships between MetS and major and minor ECGA in the Hispanic population (Hypothesis 1) and determine whether gender-ethnic subgroups moderate these r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Conversely, other studies have reported that MetS and its components, especially waist circumference and blood pressure, were associated with ECG abnormalities in the overall population [ 5 , 6 ]. On the other hand, Richard et al (2023) reported that ECG abnormalities in women, compared to men, had a higher likelihood of developing metabolic syndrome [ 9 ]. Soflaei et al (2023) reported that an increase in high-density lipoprotein cholesterol was negatively associated with ischemic ECG manifestations, while a significant positive association was observed only with an ST segment elevation [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, other studies have reported that MetS and its components, especially waist circumference and blood pressure, were associated with ECG abnormalities in the overall population [ 5 , 6 ]. On the other hand, Richard et al (2023) reported that ECG abnormalities in women, compared to men, had a higher likelihood of developing metabolic syndrome [ 9 ]. Soflaei et al (2023) reported that an increase in high-density lipoprotein cholesterol was negatively associated with ischemic ECG manifestations, while a significant positive association was observed only with an ST segment elevation [ 10 ].…”
Section: Introductionmentioning
confidence: 99%